Study of health implications effects in laser paint removal process based on PM1.0 and PM10.0 measurements - Mohammad Khairul Azhar Abdul Razab; Mohamad Suhaimi Jaafar; Azhar Abdul Rahman; Sarizam Mamat; Muhammad Iqbal Ahmad (Universiti Malaysia Kelantan, 2014)
Health implications to the staff incharged was studied by measuring mass density (N) of two types of particulate matter (PM1.0 and PM10.0) concentration produced during laser paint removal process over three different types of car coated substrate samples A, B and C. The lowest PM1.0 and PM10.0 concentrations detected for those substrate samples during 10 minute laser irradiation were 0.693 mg/m3 and 1.586 mg/m3 , which was far exceed compared to the recommendation suggested by World Health Organization (WHO). However, laser paint removal techniques was considered safe compared than chemical paint stripping technique if smooth air ventilation in workplace was properly set-up and inhalation to PM1.0 and PM10.0 was greatly prevented by using protective mask